ESTUDIO DO UN CASO MORTAL DE BRUCELLOSI - MANCERA (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1942)
The author describes a stained antigen plate test for the diagnosis of typhoid fever and 2 of the human paratyphoids The typhoid antigen is blue, the Para-A brownish yellow and the Para-B red The combination is grayish purple When mixed with serum, blu
REV MEX MED
Keywords: ESTUDIO, CASO, MORTAL, BRUCELLOSI; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS